Pengaruh Current Ratio, Debt To Equity Ratio, dan Inventory Turn Over terhadap Return On Asset pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di BEI Tahun 2014-2018 - Endalit ramayana; Abd. Wahid Rizki Sahputra -; Ivonia Florensia -; Siska Ika Sartika -; Januardin - (Jurnal Ekonomi Bisnis Manajemen Prima, 2020)
This study aims to determine the effect of Current Ratio, Debt To Equity Ratio and Inventory Turn Over on Return On Asset This study was taken from property and real estate sector companies listed on the Indonesia Stock Exchange in 2014-2018. The population contained in the property and real estate sector is 48 companies. The samples studied are 27 companies selected using purposive sampling techniques so that the total sample to be used for 5 years becomes 135 samples. The analysis method used is multiple linear regression analysis with tools help SPSS 20. The results of the F test show that simultaneously the independent variables Current Ratio, Debt To Equity ratio and Inventory Turn Over influence and significantly affect Return On Asset The t test results indicate that partially, Current Ratio, Debt To Equity Ratio and Inventory Turn Over have significant and significant influence on Return On Asset.